Exploratory behaviour towards novel objects is associated with enhanced learning in young horses - Janne Winther Christensen (Nature Portfolio, 2021)
Abstract The mechanisms underlying individual variation in learning are key to understanding the development of cognitive abilities. In humans and primates, curiosity has been suggested as an important intrinsic factor that enhances learning, whereas in domesticated species research has primarily identified factors with a negative effect on cognitive abilities, such as stress and fearfulness. This study presents the first evidence of a link between object-directed curiosity and learning performance in young horses in two very different learning tasks (visual discrimination and pressure-release). We exposed young horses (n = 44) to standardised novel object tests at 5 months and 1 year of age and found consistency in responses. Standard indicators of fearfulness (e.g. heart rate and alertness) were unrelated to learning performance, whereas exploratory behaviour towards the novel objects correlated to performance in both learning tasks. Exploratory behaviour was unreinforced in the novel object tests and likely reflects the animal’s intrinsic motivation (i.e. curiosity), suggesting that this trait is favourable for learning performance. In addition to the insights that these results provide into cognition in a domesticated species, they also raise questions in relation to fostering of curiosity in animals and the impact that such manipulation may have on cognitive abilities.